The Role of Carbonic Anhydrase in Promoting CO2 Capture and Operation of Bicarbonate-Fed Electrolyzers - Tobolovskaya, Yulia (University of Waterloo, 2022)
Capturing CO2 through chemical absorption offers a sustainable solution to mitigate rising CO2 emissions which are widely agreed to be the primary contributor to climate change. Among various capture solutions, bicarbonate solvents are favored because they are environmentally clean, have low costs, and low regeneration energies. The main limitation of using these solvents is their slow reaction kinetics with CO2 which can be improved by the enzyme, carbonic anhydrase through its reversible CO2 hydration activity. A current focus of research is on developing an integrated CO2 capture and utilization strategy that is cost-effective, sustainable as well as eco-friendly. Electrochemical conversion of captured CO2 into commercial products is a promising CO2 utilization technology that can be directly powered by sustainable renewable energy resources. Unfortunately, regenerating the CO2 gas feed from the bicarbonate capture medium is currently an energy-intensive, and expensive process. Facilitating this process requires the integration of a bicarbonate-to-CO2 promoter to directly release CO2 to the electrocatalytic surface. To this end, the thesis explores a novel bio-electrocatalytic system that feeds CO2 released through the bicarbonate dehydration activity of the enzyme, bovine carbonic anhydrase to the electrode surface comprising Au branched nanoparticles for its reduction to CO. Through electrochemical and biochemical techniques, we evaluate the performance of two different system configurations operating with external or local scale CO2 regeneration at the electrocatalytic surface. We show that isolating bovine carbonic anhydrase from the electrolyzer in a concentrated solution of KHCO3 at pH 9 allows it to function efficiently for a limited time resulting in a significant faradaic efficiency of 27 % for the CO product to be achieved. We learn however, that integrating this enzyme onto the electrode surface creates unique challenges that result in a low CO product yield. To this end, our work provides novel insights into the chemical parameters dictating the performance of bovine carbonic anhydrase and offers a valuable perspective on future research surrounding enzymatic bicarbonate utilization electrolyzers.